The Impact of augmented reality on the learning of polyhedral: an approach based on didactical engineering and instrumental genesis - Alberto Apreza Sies; Guillermina Sánchez Román; José Antonio Juárez-López (Nashir Al-Kutub Indonesia, 2025)
Despite the relevance of spatial skills in mathematics education, upper-secondary students face persistent difficulties, especially in the manipulation and conceptual understanding of three-dimensional objects. This study aims to design, implement, and analyze a didactic sequence mediated by Augmented Reality (AR) for the learning of polyhedral. The novelty lies in the analysis of the underlying cognitive processes through the framework of Instrumental Genesis, basing the design on the principles of Didactic Engineering. The research adopts a mixed-method and quasi-experimental approach. A pre-test and post-test were administered to a sample of fourth-semester upper-secondary students (n=12), complemented by an exhaustive qualitative analysis of the interaction with the GeoGebra 3D AR tool. Pre-test findings confirmed student weaknesses, showing only 25% success on measurement and dimensioning tasks. The post-intervention analysis demonstrated a significant and positive impact of the didactic sequence, evidenced by the total adaptation and instrumentalization of the AR tool. This resulted in a favorable evolution of cognitive schemes and a noticeable improvement in spatial visualization skills. The findings suggest that successful technological integration in 3D geometry must be guided by rigorous theoretical design and a detailed analysis of knowledge construction mediated by the instrument, providing empirical evidence for the implementation of AR in the mathematics classroom.